Step-by-step Solution

Solve the trigonometric equation $\frac{\sec\left(x\right)-1}{1-\cos\left(x\right)}=\sec\left(x\right)$

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Step-by-step explanation

Problem to solve:

$\frac{\sec\left(x\right)-1}{1-\cos\left(x\right)}=\sec\left(x\right)$

Learn how to solve trigonometric equations problems step by step online.

$\sec\left(x\right)-1=\sec\left(x\right)\left(1-\cos\left(x\right)\right)$

Unlock this full step-by-step solution!

Learn how to solve trigonometric equations problems step by step online. Solve the trigonometric equation (sec(x)-1)/(1-cos(x))=sec(x). Multiply both sides of the equation by 1-\cos\left(x\right). Applying the secant identity: \displaystyle\sec\left(\theta\right)=\frac{1}{\cos\left(\theta\right)}. Applying the secant identity: \displaystyle\sec\left(\theta\right)=\frac{1}{\cos\left(\theta\right)}. Multiply the fraction and term.

Final Answer

true
$\frac{\sec\left(x\right)-1}{1-\cos\left(x\right)}=\sec\left(x\right)$

Related formulas:

1. See formulas

Time to solve it:

~ 0.07 s (SnapXam)

Related topics:

Trigonometric Equations